Brown dwarf companions in microlensing binaries detected during the 2016-2018 seasons - Han, Cheongho; Ryu, Yoon-Hyun; Shin, In-Gu; Jung, Youn Kil; Kim, Doeon; Hirao, Yuki; Bozza, Valerio; Albrow, Michael D.; Zang, Weicheng; Udalski, Andrzej; Bond, Ian A.; Chung, Sun-Ju; et al. (Astronomy and astrophysics, 2022)
Aims. With the aim of finding microlensing binaries containing brown dwarf (BD) companions, we investigate the microlensing survey data collected during the 2016-2018 seasons. Methods. For this purpose, we first modeled lensing events with light curves exhibiting anomaly features that are likely to be produced by binary lenses. We then sorted out BD companion binary-lens events by applying the criterion that the companion-to-primary mass ratio is q ≲ 0.1. With this procedure, we identify six binaries with candidate BD companions: OGLE-2016-BLG-0890L, MOA-2017-BLG-477L, OGLE-2017-BLG-0614L, KMT-2018-BLG-0357L, OGLE-2018-BLG-1489L, and OGLE-2018-BLG-0360L. Results. We estimated the masses of the binary companions by conducting Bayesian analyses using the observables of the individual lensing events. According to the Bayesian estimation of the lens masses, the probabilities for the lens companions of the events OGLE-2016-BLG-0890, OGLE-2017-BLG-0614, OGLE-2018-BLG-1489, and OGLE-2018-BLG-0360 to be in the BD mass regime are very high with PBD > 80%. For MOA-2017-BLG-477 and KMT-2018-BLG-0357, the probabilities are relatively low with PBD = 61% and 69%, respectively.
Gesehen am 01.02.2023